Description of characteristics and knowledge of prenatal yoga in trimester iii pregnant women at Kasih Bunda Sunggal Clinic 2024 - Oktaviance S., R.; Siburian, Nelly; Ambarita, Bernadetta; Arisandi, Ermaway (Institute of Computer Science (IOCS), 2024)
In the third trimester of pregnancy, mothers experience changes that can cause discomfort. Back pain occurs and increases with gestational age. Back pain is more pronounced at 36 weeks of gestation. Prenatal yoga is a series of exercises specially designed for pregnant women which aims to train the body for muscle elasticity and train breathing. The purpose of this study is to determine how the knowledge of third trimester pregnant women who do prenatal yoga with back pain. Sample collection is done by accidental sampling using the description method with 12 people. Third trimester pregnant women age 26-35 years are 9 people (75%), based on parity, there are 11 respondents (91.7%), and 1 person (8.3%) is with primipara. Mothers do not work, namely 10 people (83.7%) and 2 people (16.3%) worked as self-employed. Based on sufficient income, 11 people (91.7%) are obtained, and based on education, the majority of pregnant women graduated from high school, namely 11 people (91.7%). Pregnant women who experience back pain are 12 people (100%) and pregnant women who do not do prenatal yoga are 9 people (75%). The knowledge of pregnant women who do prenatal yoga with back pain is mostly good as many as 8 people (66.7%). The conclusion of this study is that prenatal yoga can reduce complaints of back pain in mothers of trimeser III.